Cariprazine Orodispersible Tablet: A New Formulation for Cariprazine - Meszár, Viktória; Magyar, Gabriella; Pásztor, Gabriella Mészárosné; Szatmári, Balázs; Péter, Krisztina; Marton, Lívia; Dombi, Zsófia B; Barabássy, Ágota (Pharmacopsychiatry, 2024)
Cariprazine is an atypical dopamine receptor partial agonist antipsychotic available in the form of capsules. Although capsules are one of the most desirable routes of administration, there are certain situations (e. g., in an acute psychiatric setting, or when swallowing difficulties, or liquid shortages are present) when they cannot be administered. Therefore, alternative solutions like orodispersible tablets are needed. This study aimed to investigate the bioequivalence of a newly developed orodispersible tablet to the commercially available hard gelatine capsule of cariprazine 1.5 mg. This was a phase I, open-label, randomized, single-dose bioequivalence study. It had a 2-period, 2-sequence, cross-over design, where each subject received one test and one reference product in a randomized sequence, separated by a wash-out period of 55 days. Blood sampling was performed over 72 h after dosing. Cariprazine concentrations were analyzed by a validated HPLC-MS/MS method. Standard bioequivalence statistics was applied to PK parameters calculated by non-compartmental analysis. Safety measures were analyzed descriptively. Pharmacokinetic data of 43 healthy volunteers and safety data of 54 subjects was analyzed. Cariprazine AUC and C geometric mean ratios were 117.76% and 100.88%, respectively. The 90% confidence intervals were within the pre-defined bioequivalence acceptance limits of 80.00% - 125.00%. Safety data was in line with the Summary of Product Characteristics of Cariprazine. The result of this clinical trial proved the bioequivalence of the new orodispersible tablet formulation when compared to hard gelatine capsules, enabling an alternative option for treatment of those suffering from schizophrenia.